Nondestructive quantification of moisture in powdered low-rank coal by a unilateral nuclear magnetic resonance scanner. Issue 5 (4th May 2022) - Nakashima, Yoshito; Sawatsubashi, Tetsuya; Fujii, Shuji
ABSTRACT: Moisture content in coal powder is a critical index because it controls the difficulty of coal handling and ultimately its combustion efficiency in coal-fired power plants. A unilateral proton nuclear magnetic resonance (NMR) scanner was applied in a laboratory to nondestructively quantify moisture content in powdered samples of brown and subbituminous coals. Due to the open geometry of the sensor unit, the scanner allows the nondestructive moisture quantification of a portion several millimeters below the surface of a large sample. Proton transverse relaxation was measured by the unilateral NMR scanner, and obtained moisture content values were compared with those by a conventional bilateral NMR apparatus. The comparison showed reasonable agreement with a root mean square residual of 4.1 wt.%H2 O for a moisture content range of > 12 wt.%H2 O (wet basis). This moisture-quantification performance by unilateral NMR is sufficient for the quality control of wet coal having a critical value of approximately 30 wt.%H2 O in terms of the handling property (flow-ability). Because unilateral NMR requires no specific sample preparation, such as sample insertion into tubes, the system is potentially applicable to in-situ nondestructive monitoring of the coal moisture in power plants to contribute to improved efficiency of handling and combustion.